Weight Dynamics in Immature Anogeissus, Tectona and Terminalia - Kandya, A. K. (Indian Forester, 1974)
The present deals with the study of aerial biomass of 3 dominant forest tree species of Sagar i.e. Anogeissus latifolia, Tectona grandis and Terminalia tomentosa of about 20 years in age. In this investigation it bas been observed that the total biomass of all the plant parts in the above species is approximately equal (80-83 kg). On the whole it has been estimated that about 55% of the aerial biomass is removed from the forest ecosystem as timber, about 25% is used as fuel or coal while the remaining 20% of the crop which is of no use for the forest contractors is left inside the forests. This coasists of twigs and leaves and gets decomposed subsequently. 8% of the biomass falls in the from of leaf litter every year if such a forest is left uncut. On an unit volume basis the weights of wood and bark of Terminalia are the largest. There is a positive correlation between the leaf dry weight and its area while the percentage of bark and the girth of trunk show a negative correlation.